1-(3-Hydroxypropyl)-3-phenylquinoxalin-2(1H)-one - Nadeem Abad (IUCrData, 2018)
In the title molecule, C17H16N2O2, the quinoxaline portion is slightly folded about the N...N axis with an angle of 4.27 (4)°. In the crystal, O—H...O and weak C—H...O hydrogen bonds link molecules along the b-axis direction. In addition, two sets of weak C—H...π(ring) interactions form a two-dimensional `step' motif parallel to the bc plane.